2000
DOI: 10.1002/1097-0010(20010101)81:1<10::aid-jsfa779>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Why do we like what we like?

Abstract: Why do we find certain foods more pleasurable than others? Interactions of food components with human biology and with social and eating contexts give rise, in some predictable ways, to relatively stable individual food likes. While sensory and consumer research have traditionally focused on measuring existing likes, a better understanding of their basic determinants can provide ideas and tools to better predict and influence how likes may develop and change. The liking for a particular food or set of foods la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 46 publications
0
55
0
4
Order By: Relevance
“…Foods higher in saturated fat, sodium or total fat were not consistently preferred by these pre-school children, which tends to align with consumption recommendations. These findings were not expected given a reported biological bias towards foods higher in fat and possibly salt in children 18,19 . However, previous research by Wardle et al 23 showed that children's everyday food preferences did not cluster according to simple factors like sweetness or fattiness, but rather they may have had something more to do with complex cognitive structures, and that finding is somewhat supported here.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Foods higher in saturated fat, sodium or total fat were not consistently preferred by these pre-school children, which tends to align with consumption recommendations. These findings were not expected given a reported biological bias towards foods higher in fat and possibly salt in children 18,19 . However, previous research by Wardle et al 23 showed that children's everyday food preferences did not cluster according to simple factors like sweetness or fattiness, but rather they may have had something more to do with complex cognitive structures, and that finding is somewhat supported here.…”
Section: Discussionmentioning
confidence: 63%
“…The Extra Foods group had the highest average energy density and sugar whereas the Vegetables group was low in energy density and sugar; and children tended to like foods higher in energy density and sugar. Children learn to like energy-dense foods likely through positive post-ingestive consequences (feelings of satiation) 16,17 and have an innate predisposition towards sweet 19 . Whilst this pattern of preferences is contrary to international dietary recommendations for consumption (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the food items apple and chocolate eating were found to improve mood but chocolate's effect was stronger (Macht and Dettmer, 2006) Chocolate eating reduced negative mood after watching sad film; no effect was identified on positive mood Bad mood alleviated after eating palatable chocolate (up to 70% cocoa)-but the effect was very short-lived. Generally chocolate and filled chocolate are known for the arousal of sensory pleasure due to the specific melting behaviour, aroma and taste (Januszewska and Viaene, 2002;Mela, 2000;Parker et al, 2006, Pelsmaeker et al, 2014. Several authors indicate that the popularity of chocolate is closely related to the emotions it evokes with the consumer (Macht and Dettmer, 2006;Parker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…O sabor, por combinações de atributos sensoriais, é adquirido como resultado da associação com outros estímulos e pode ser determinado por regras culturais e sociais (Mela, 2000). Para North e Hargreaves (1996), e Terwogt e Van Grinsven (1991), as qualidades eliciadoras dos estímulos musicais interagem com as características contextuais da situação, determinando respostas específicas.…”
unclassified
“…O julgamento das modalidades sensoriais gustativas e auditivas varia, tanto com o contexto em que ocorrem, como também com as atitudes, crenças e expectativas do avaliado (Mela, 2000). Rozin, Riklis e Margolis (2004) explicam que a variação no julgamento resulta de experiências aleatórias, tais como consumir um alimento ruim, ou ouvir notícias boas ou ruins, enquanto se ouve uma música específica.…”
unclassified